Agent-based modelling of coalition formation in energy micro-grids. (2017) - Yasir, Muhammad; Purvis, Martin; Purvis, Maryam; Savarimuthu, Bastin Tony Roy
In micro-grids energy is generated and consumed locally from intermittent renewable energy sources. Because of energy variability, sometimes there are energy surpluses and sometimes deficits. The ill effects of intermittency can be reduced by trading energy by means of a connected electricity grid. This work introduces an alternative solution by forming coalitions among micro-grid communities, since mainline electricity grids are subject to faults and outages. These coalitions can withstand power outages by sharing energy among them. We present a model for dynamic micro-grid coalition formation and demonstrate that the model is scalable and preserves the autonomy of individual micro-grids by enabling them to join and depart from a coalition. Our empirical studies demonstrate that our model reduces overall 'discomfort' (a notion defined in the paper), so that even when all participating micro-grids in a coalition experience deficits, they can share energy so that their overall discomfort is minimised.